2016
DOI: 10.3389/fnint.2016.00032
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation from Cochlear Implant Electrodes Assists with Recovery from Asymmetric Perceptual Tilt: Evidence from the Subjective Visual Vertical Test

Abstract: Vestibular end organ impairment is highly prevalent in children who have sensorineural hearing loss (SNHL) rehabilitated with cochlear implants (CIs). As a result, spatial perception is likely to be impacted in this population. Of particular interest is the perception of visual vertical because it reflects a perceptual tilt in the roll axis and is sensitive to an imbalance in otolith function. The objectives of the present study were thus to identify abnormalities in perception of the vertical plane in childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 50 publications
2
9
1
1
Order By: Relevance
“…These results suggest a role for CI stimulation beyond the auditory system, in particular, for improving vestibular/balance function. 118 While our approach has been to aim to extend the functionality of the intra-cochlear electrode array, several groups have been aiming to more directly and specifically activate the vestibular end organs using separate electrode arrays targeting the labyrinth. Early experiments with such devices began in animals [119][120][121] and demonstrated the capacity to restore the VOR and function of the semicircular canals.…”
Section: Functional Impact Of Vestibular and Balance Impairmentmentioning
confidence: 99%
“…These results suggest a role for CI stimulation beyond the auditory system, in particular, for improving vestibular/balance function. 118 While our approach has been to aim to extend the functionality of the intra-cochlear electrode array, several groups have been aiming to more directly and specifically activate the vestibular end organs using separate electrode arrays targeting the labyrinth. Early experiments with such devices began in animals [119][120][121] and demonstrated the capacity to restore the VOR and function of the semicircular canals.…”
Section: Functional Impact Of Vestibular and Balance Impairmentmentioning
confidence: 99%
“…As vestibular dysfunction is prevalent in severe-to-profound hearing loss, protocols to minimize the risk for vestibular loss due to CI surgery have been proposed [ 9 ]. In contrast to surgery, electrical stimulation from the CI has, however, been suggested to improve vestibular function [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gnanasegaram et al (48) demonstrated conspicuous values in the SVV test ∼1 year postoperatively in 45% of patients after cochlear implantation. In the study presented here, these results could not be confirmed, neither in patients with nor without vertigo.…”
Section: Subjective Visual Verticalmentioning
confidence: 98%